Polymorphisms and Haplotypes in the Interleukin-4 Gene are Associated With Chronic Periodontitis in a Brazilian Population - Anovazzi, Giovana [UNESP]; Kim, Yeon J. [UNESP]; Viana, Aline C. [UNESP]; Curtis, Karen M. C. [UNESP]; Orrico, Silvana Regina Perez [UNESP]; Cirelli, Joni Augusto [UNESP]; Scarel-Caminaga, Raquel M. [UNESP] (Amer Acad Periodontology, 2010)
Background: Some haplotypes in the interleukin-4 (IL4) gene were reported to influence IL-4 cytokine production and were associated with inflammatory diseases. Association studies focusing on IL4 gene polymorphisms and periodontal disease provided conflicting results. The aim of this study is to investigate whether IL4 gene polymorphisms and haplotypes were related to chronic periodontitis in a Brazilian population.Methods: The polymorphisms -590(C/T) and +33(C/T) in the IL4 gene were identified by polymerase chain reaction (PCR) and restriction fragment-length polymorphism methods; the variable number of tandem repeats (VNTR) was identified by PCR. To assess the differences between the periodontitis group (n = 125) and control group (n = 125), the chi(2) test was used to assess genotype and allele distributions of individual polymorphisms. For haplotypes reconstructed by an expectation-maximization algorithm, the CLUMP program and Fisher exact test were used. Multivariate logistic regression modeling was used to assess the association of age, gender, smoking status, and polymorphism/haplotype with periodontitis.Results: The -590(T), +33(C), and insertion (I) of 70-base pair (bp) alleles and genotypes were more prevalent in the periodontitis group, even after adjusting for covariates. The -590, +33, and insertion (TCI) haplotype was associated with a susceptibility to periodontitis (adjusted odds ratio [OR(adjusted)] = 2.68; 95% confidence interval [CI] = 1.50 to 4.80) as was the genotype TCI/CCI (OR(adjusted) = 5.27; 95% CI = 2.28 to 12.18), whereas the TTD (OR(adjusted) = 0.48; 95% CI = 0.26 to 0.91), CTI (OR(adjusted) = 0.28, 95% CI = 0.11 to 0.70), and TTD/CTI (OR(adjusted) = 0.29; 95% CI = 0.08 to 1.13) genotypes were a associated with protection against the development of chronic periodontitis.Conclusion: Significant associations between alleles, genotypes, and haplotypes of polymorphisms in the IL4 gene and chronic periodontitis were verified in Brazilian individuals. J Periodontol 2010;81:392-402.
Keywords: Disease susceptibility; genetics; periodontitis